2018
DOI: 10.1016/j.sapharm.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trials covering pharmaceutical care and medicines management: A systematic review of literature

Abstract: 2 Objective 3To review the effects of pharmaceutical care on hospitalizations, mortality and clinical outcomes in 4 patients. 5 Methods 6Systematic searches were conducted in MEDLINE, EMBASE and International Pharmaceutical Abstracts 7 (IPA) databases to identify studies that were published between 2004 and January 2017. Studies 8 included in this review were randomized controlled trials (RCTs) that spanned across both community and 9 hospital settings. Using strict inclusion/exclusion criteria studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 69 publications
1
23
0
4
Order By: Relevance
“…According to the participants, the presence of a specialist pharmacist in their health care team and the implementation of pharmaceutical care may positively influence the adherence of the patients to their treatment. This was consistent with other studies which concluded that applying pharmaceutical care services shown positive outcomes with improving medication use, adherence and surrogate outcome 30‐32 . Pharmaceutical care services were found to give the pharmacists the opportunity to improve HIV patients adherence rate and to enhance treatment response with higher CD4 percentage 32 .…”
Section: Discussionsupporting
confidence: 90%
“…According to the participants, the presence of a specialist pharmacist in their health care team and the implementation of pharmaceutical care may positively influence the adherence of the patients to their treatment. This was consistent with other studies which concluded that applying pharmaceutical care services shown positive outcomes with improving medication use, adherence and surrogate outcome 30‐32 . Pharmaceutical care services were found to give the pharmacists the opportunity to improve HIV patients adherence rate and to enhance treatment response with higher CD4 percentage 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Mathumalar et al (2011), Patterson et al (2012), Lee et al (2013), Sáez-Benito et al (2013), Cooper et al (2015), Olaniyan et al (2015), and Babar et al (2017) presented evidence for clinical outcomes related to the reduction of polypharmacy, medication errors, and prescription of potentially inappropriate medications; improvement of the use of appropriate and safe medications; and improvement of adherence. Lee et al (2013) also found data on clinical outcomes regarding the reduction of drug-related problems, adverse drug events, adverse drug reactions, drug-drug interactions, and drug-related negative health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The underlying recommendation was to move toward a patient-centered philosophy of clinical practice aimed at improving therapy outcomes. From its inception, the primary goal of pharmaceutical care was to give pharmacists the opportunity to move beyond the role of merely dispensing the right drug [21]. Later on, even the term itself was perceived as a limit against the spread of pharmaceutical care beyond the pharmacists' professional world [22].…”
Section: Clinical Pharmacy and Pharmaceutical Carementioning
confidence: 99%